Microalgae: An emerging source of energy based bio-products and a solution for environmental issues. (May 2017) - Katiyar, Richa; Gurjar, B.R.; Biswas, Shalini; Pruthi, Vikas; Kumar, Nalin; Kumar, Prashant
Abstract: The microalgae biomass is emerging as a potential source of energy and bioproducts with several advantages over conventional crops in terms of its ability to produce ~300-times more renewable oil. Microalgae also have a high photosynthetic response, product accumulation rate and biomass production rate compared with other energy crops. Microalgae have the ability to grow on nonagricultural soil using wastewater instead of drinking water. Furthermore, microalgae have high capability to fix carbon dioxide from the environment. Microalgae-based bioproducts have different applications in pharmaceuticals, food and feed industries, and agricultural and transportation sectors. The key objectives covered in this review pertain to the role of microalgae to (i) maintain food chain, (ii) conservation of land and water resources in the environment with sequestration of CO2, (iii) production of energy in the form of biodiesel with zero waste, and (iv) simultaneous release of higher oxygen to the environment compared with other energy crops.